2020
DOI: 10.14686/buefad.541061
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mathematical Skills of 60-72 Months Old Children Attending Preschool Education in Terms of Some Variables

Abstract: The aim of this study is to determine mathematical skills of 60-72 months old children attending preschool education and whether these skills make a significant difference in terms of gender, mother education, father education, number of siblings, duration of preschool education and socio-economic status of family. The research was designed with descriptive scanning model. The sample of the study consisted of 372 children, 60-72 months of age, who were randomly selected from each of official independent kinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Research has found that SES-related math gaps are present in the population of Turkish children. Several studies found that mathematical knowledge was less extensive in low-SES children than in their higher-SES peers (Çelik, 2015;Kandır & Koçak Tümer, 2013;Karaman & İvrendi, 2015;Polat Unutkan, 2007;Tabuk et al, 2018;Tok & Ünal, 2020). SES differences in early spatial and geometric knowledge, including knowledge of two-dimensional shapes, have also been observed (Aslan et al, 2012;Uyanık Aktulun & Keser, 2021).…”
Section: The Ses-related Math Gap In Türkiyementioning
confidence: 99%
“…Research has found that SES-related math gaps are present in the population of Turkish children. Several studies found that mathematical knowledge was less extensive in low-SES children than in their higher-SES peers (Çelik, 2015;Kandır & Koçak Tümer, 2013;Karaman & İvrendi, 2015;Polat Unutkan, 2007;Tabuk et al, 2018;Tok & Ünal, 2020). SES differences in early spatial and geometric knowledge, including knowledge of two-dimensional shapes, have also been observed (Aslan et al, 2012;Uyanık Aktulun & Keser, 2021).…”
Section: The Ses-related Math Gap In Türkiyementioning
confidence: 99%